Itinerant Jewish and Arabic Trading in the Dene’s North, 1916-1930 - Colpitts, George (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
In late nineteenth century and especially in the interwar years, “free traders” took advantage of better transport systems to expand trade with Dene people in the Athabasca and Mackenzie Districts. Well versed in fur grading and supported by credit in the expanding industrializing fur industry in the south, “itinerant” peddlers worked independently and often controversially alongside larger capitalized fur companies such as the Hudson’s Bay Company. A large number of these newcomers were Jews. This article suggests that Jews and, to a lesser extent, Lebanese and other Arabic traders became critical in the modernization of the Canadian North. They helped create an itinerant trader-Dene “contact zone” where the mixed meaning of credit, cash, and goods transactions provided northern Aboriginal trappers the means to negotiate modernism on their own terms in the interwar years. However, by the late 1920s, the state, encouraged by larger capitalized companies, implemented policies to restrict and finally close down this contact zone. The history of itinerant trading, then, raises questions about the long-term history of capitalism and co-related economic neo-colonialism in the Canadian north and their impact on First Nations.